2020
DOI: 10.3389/fbioe.2020.00462
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3D-Printed Sulfated Chitosan Modified Bioresorbable Stents for Coronary Artery Disease

Abstract: Bioresorbable polymeric stents have attracted great interest for coronary artery disease because they can provide mechanical support first and then disappear within a desired time period. The conventional manufacturing process is laser cutting, and generally they are fabricated from tubular prototypes produced by injection molding or melt extrusion. The aim of this study is to fabricate and characterize a novel bioresorbable polymeric stent for treatment of coronary artery disease. Polycaprolactone (PCL) is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Generation of realistic and dynamic models is of clinically important for cardiovascular disease as simulation of hemodynamic blood flow in these 3D cardiovascular models plays a crucial role in creating a realistic environment that can mimic the real physiological situation. Some recent studies already demonstrated the dynamic mechanical properties of 3D printing materials in coronary artery disease and coronary stents [ 119 , 120 , 121 ]. 3D printed bioresorbable stents using polymer materials such as polylactic acid (PLA) or polycaprolactone (PCL) have shown good compatibility with blood and cells, and they can be used to print coronary stents for treating coronary artery disease [ 120 ].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of realistic and dynamic models is of clinically important for cardiovascular disease as simulation of hemodynamic blood flow in these 3D cardiovascular models plays a crucial role in creating a realistic environment that can mimic the real physiological situation. Some recent studies already demonstrated the dynamic mechanical properties of 3D printing materials in coronary artery disease and coronary stents [ 119 , 120 , 121 ]. 3D printed bioresorbable stents using polymer materials such as polylactic acid (PLA) or polycaprolactone (PCL) have shown good compatibility with blood and cells, and they can be used to print coronary stents for treating coronary artery disease [ 120 ].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Some recent studies already demonstrated the dynamic mechanical properties of 3D printing materials in coronary artery disease and coronary stents [ 119 , 120 , 121 ]. 3D printed bioresorbable stents using polymer materials such as polylactic acid (PLA) or polycaprolactone (PCL) have shown good compatibility with blood and cells, and they can be used to print coronary stents for treating coronary artery disease [ 120 ]. Guerra et al produced 3D printed composite stents using PLA and PCL materials.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…It is well known that sulfated chitosan enhances the bioactivity of the material [34] . In a recent study, Qiu et al [35] designed a 3D-printed bioresorbable stent using polycaprolactone (PCL), surface modified with sulfated chitosan. Chlorosulfuric acid (HClSO 3 ) was used to sulfonate chitosan at 70 ºC.…”
Section: Chitosan-based Hydrogels For Pcimentioning
confidence: 99%
“…Adapted with permission from Qiu et al . [35] to the treatment of the cardiac tissues. A 3D porous network with pore size of 20 ± 3 μm and 32 ± 5 μm was respectively obtained for CS/CG and GQDs-CS/CG hydrogels.…”
Section: Chitosan-based Hydrogels For Pcimentioning
confidence: 99%
See 1 more Smart Citation